Ageing and literacy skills: Evidence from Canada, Norway and the United States - David A. Green; W. Craig Riddell (Institute for the Study of Labor (IZA), 2012)
We study the relationship between age and literacy skills in Canada, Norway and the U.S. &- countries that represent a wide range of literacy outcomes - using data from the 1994 and 2003 International Adult Literacy Surveys. In cross-sectional data there is a weak negative partial relationship between literacy skills and age. However, this relationship could reflect some combination of age and cohort effects. In order to identify age effects, we use the 1994 and 2003 surveys to create synthetic cohorts. Our analysis shows that the modest negative slope of the literacy-age profile in cross-sectional data arises from offsetting ageing and cohort effects. Individuals from a given birth cohort lose literacy skills after they leave school at a rate greater than indicated by cross-sectional estimates. At the same time, more recent birth cohorts have lower levels of literacy. These results suggest a pervasive tendency for literacy skills to decline over time and that these countries are doing a poorer job of educating successive generations. All three countries show similar patterns of skill loss with age, as well as declining literacy across successive cohorts. The countries differ, however, in the part of the skill distribution where falling skills are most evident. In Canada the cross-cohort declines are especially large at the top of the skill distribution. In Norway declining skills across cohorts are more prevalent at the bottom of the distribution. In the U.S. the decline in literacy skills over time is most pronounced in the middle of the distribution.
urn:nbn:de:101:1-201207125574
Keywords: I20; J14; J24; 330; human capital; cognitive skills; literacy; ageing; Analphabetismus; Bildungsniveau; Altersgruppe; Kanada; Norwegen; USA